(untitled) (Global Journal of Medical Research, 2020)
Japan is a supper-aged society, and many older adults need home care. To provide meals safely at home, the viscosity of meals suitable for the elderly required. Therefore, in this study, the viscosity was measured by combining two types of thickeners that can purchase at pharmacies and three types of care foods. The thickener used this time has almost the same price and content, but the many included material is different. Thickener A was rich in watersoluble dietary fiber, and thickener B was rich in thickening polysaccharides. The three types of foods were foods with high carbohydrate content, high lipid content, and high water content. As a result, thickening agent B, which is rich in thickening polysaccharides, was able to maintain the viscosity better than thickening agent A if a thickening agent added at a low (100g food per 1g thickening) concentration to foods rich in lipids and water. However, when the addition amount of the thickener was large, the thickener A and the thickener B showed almost the same viscosity. It will be necessary to increase the number of samples and clarify the differences due to the combinations.